2011
DOI: 10.1038/hr.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

Salt intake in 3-year-old Japanese children

Abstract: Salt restriction is widely recommended for the prevention and management of hypertension. It is very important to reduce salt intake during childhood. This survey was conducted to investigate salt intake in Japanese children. The study subjects, totalling 1424, comprised 3-year-old children who received health checkups conducted by a public health center. Using first-morning urine samples, urinary concentrations of sodium, potassium and creatinine were measured. Additionally, the participants' parents filled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
(27 reference statements)
0
16
3
Order By: Relevance
“…We hypothesized that living with grandparents could result in higher salt intake of the children, as elderly people in Japan tend to consume more salt than young people do, and their taste preference for salt might influence salt consumption in their grandchildren. Moreover, it has been suggested that having older siblings might be related to increased salt intake in children, though this was based only on univariate analysis . It is possible that older siblings who enjoy salty snacks are likely to expose younger siblings to them early, but our analysis found no significant associations between the daily salt intake of the children and family structure.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…We hypothesized that living with grandparents could result in higher salt intake of the children, as elderly people in Japan tend to consume more salt than young people do, and their taste preference for salt might influence salt consumption in their grandchildren. Moreover, it has been suggested that having older siblings might be related to increased salt intake in children, though this was based only on univariate analysis . It is possible that older siblings who enjoy salty snacks are likely to expose younger siblings to them early, but our analysis found no significant associations between the daily salt intake of the children and family structure.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the ideal method for estimating daily salt excretion is 24‐hour urine collection, it is very difficult to collect 24‐hour urine from a 3‐year‐old child; according to a previous study, only about half of such attempts are successful . We therefore used a formula developed by Morinaga and colleagues that estimates daily salt excretion based on a first morning urine sample. The formula, which assumes a 24‐hour urinary creatinine excretion in 3‐year‐old children of 300 mg, is as follows: 24‐hour salt excretion (g/d) = 0.0585 × 300 × (NaM/CrM), where NaM is the sodium concentration in the first morning urine (mEq/L) and CrM is the creatinine concentration in the first morning urine (mg/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 79 children aged 3 to 5 years, Haga and colleagues used a 24‐hour urine collection method and reported that the urinary sodium excretion level was 79 mmol/d (salt: 4.6 g/d). Morinaga and colleagues estimated the urinary sodium excretion of 1424 children aged 3 years using spot urine samples, and reported the mean value as 75 mmol/d (salt: 4.4 g/d). However, these results for sodium intake and excretion are from 1‐ to 2‐day studies, which may not reflect the average intake/excretion levels of sodium and potassium because these fluctuate within and between children .…”
Section: Introductionmentioning
confidence: 99%
“…All participants (358 participants; boys 193, girls 165) underwent anthropometric measurement (weight, height, obesity index) and the measurement of Systolic blood pressure (SBP) and diastolic blood pressures (DBP) by an automatic sphygmomanometer. Urinary sodium, potassium and creatinine concentrations using the first morning urine specimen were measured, and the 24hr intake of sodium and potassium were estimated (2,3) . Continuous variables were expressed as the mean ± standard deviation.…”
mentioning
confidence: 99%